DETERMINAN GANGGUAN KAPASITAS FUNGSI PARU-PARU PADA PERAJIN BATU BATA MERAH DI KABUPATEN BADUNG - Pramesti, I Gusti Agung Ayu Vintan; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH, 2021)
ABSTRACT Red brick crafters are the informal sectors, namely daily laborers and piece workers who are at risk of lung capacity function disorders as a result of dust exposure during the work. This study’s aim is to determine relationship between individual characteristics and exposure to dust with the lung capacity function disorders in red brick crafters in Badung Regency. This study’s designs is quantitative analytic with cross-sectional study method. Determination sample using consecutive sampling method (n= 42 peoples). Data about age, daily hours of work, working period, smoking habits, and use of PPE are collected by questionnaire, height measured by microtoise, weight by spring scales, dust exposure by Personal Dust Sampler, and lung capacity function disorders with spirometer. Data is analyzed univariable, bivariable with Chi-square, and multivariable with multiple logistic regression to analyze factors that related to lung capacity function disorders. The results showed 92,86% crafters had lung capacity function disorders. Multivariable analysis showed that dust exposure correlate with lung capacity function disorders but the signification is low (AOR=18,18; 95%CI=1,02-324,8; p=0,004). As an effort to prevent lung capacity function disorders, crafters should be aware of the risk on the worksite and also keep doing prevention. Keywords : Crafters, Pulmonary Function, Dust